Studi Literatur Tentang Perkembangan dan Karakteristik Anak Usia Dini - Al Melia Putri Kuku; Sulastri Libunelo; Sri Muliyana Taha; Indawati Pakaya; Pupung Puspa Ardini; Sri Rawanti (Inovasi Pendidikan dan Anak Usia Dini, 2025)
Early childhood development is a crucial phase in human life, marked by rapid changes in physical, cognitive, social, and emotional domains. This study aims to explore in depth the growth process and unique characteristics of early childhood using a qualitative approach through literature review methods. The findings reveal that young children possess high curiosity, vivid imagination, and strong dependence on adults in learning and social behavior formation. Physical development progresses rapidly, while cognitive and socio-emotional development are significantly influenced by environmental stimulation, parenting style, and social interaction. Understanding these characteristics and developmental needs allows educators and parents to implement more effective approaches in supporting children's growth. This study emphasizes the importance of creating a safe, supportive, and responsive environment as a foundation for future educational success and character building.